Fatigue behaviour of a structural steel under non-proportional multiaxial loading - Reis,Luís (2008)
This paper reports experimental studies on the fatigue behaviour of 42CrMo4 steel under non-proportional loading conditions. Although the 42CrMo4 steel is widely used in complex stressed components such as shafts, etc, most of the studies in the literature were on the uni-axial fatigue behaviour of this steel. The objective of this work is to study the mechanical behaviour of the steel 42CrMo4 under specified multiaxial fatigue loading conditions, which will allow a better understanding of the ratio between normal and shear stress, and validate the fatigue damage models. A series of tests were carried out in load control for several multiaxial fatigue loading paths. Experimental results show that the ratio between normal stress and shear stress components has a strong influence to fatigue damage and consequently to fatigue life. Multiaxial fatigue damage models based on the shear stress amplitude are applied to correlate the test results, improved correlation results are shown.